Evaluation of anti-botulinum neurotoxin single domain antibodies with additional optimization for improved production and stability. (1st September 2017) - Shriver-Lake, Lisa C.; Zabetakis, Dan; Goldman, Ellen R.; Anderson, George P.
Abstract: Botulinum neurotoxin (BoNT) is a highly potent and lethal toxin, which even in minute quantities can lead to death. BoNT occurs in seven well described serotypes, A-G, and it is critical to not only detect the presence of BoNT, but also to determine the serotype to which a person has been exposed, as the degree of toxicity and persistence of symptoms varies greatly between the various types. Recently, Conway et al. 2010 developed single domain antibodies (sdAb), the recombinant variable domains of heavy-chain-only antibodies derived from camelids, for the detection of all seven serotypes of BoNT; identifying pairs of sdAb for each serotype they demonstrated the sensitive detection of each toxin. Using the sequence information provided in that work, fourteen of their sdAb were recreated with one goal being confirmation of their binding ability and specificity for the seven serotypes of BoNT. This was accomplished using a direct binding assay with the toxins immobilized on microtiter plates. In addition, the melting temperatures and production yields from E. coli shake flask fermentation were determined for each of the sdAb produced. In several instances, alternatives or variants of the previously described sdAb were prepared, either to improve the stability or production yields of the anti-BoNT sdAb. Insertion of four framework 1 point mutations (1E or D, 3Q, 5V, and 6E) gave repeated improvement in thermal stability by 5–9 °C, offering a method for increasing sdAb melting temperatures. This work provides for the independent verification of the ability of these sdAb to recognize all seven serotypes of BoNT, furnishing melting temperature, relative affinity, and production yield information that will allow for their future utilization with increased confidence. Highlights: Validated pairs of previously selected single domain antibodies for all seven serotypes of botulinum neurotoxin. Evaluated stability, binding ability, relative affinity for toxin/toxin-complexes and production yields. Mutations of clones for BoNT C, E, F and G improved melting temperatures and/or production yields. Four framework 1 amino acids (1E or D, 3Q, 5V, and 6E), were confirmed to confer thermal stabilization to sdAb of ≥5 °C.